Comparison between two types of needles for Endoscopic Ultrasound (EUS)‐guided fine aspiration biopsy of pancreatic and upper gastrointestinal masses. Issue 3 (18th December 2019) - Alkhateeb, Khaled; Lee, Beatrice B.; Alatassi, Houda; Sanders, Mary A.; Omer, Endashaw M.; McClave, Stephen A.; Fraig, Mostafa
Abstract: Background: EUS‐guided fine‐needle aspiration (FNA) has long been the main method for sampling pancreatic lesions. Recently, the method of fine‐needle biopsy (FNB) was introduced in practice, allowing for the acquisition of tissue cores while aspirating the lesion. We hereby report our experience with a new FNB needle compared with the standard FNA needle. Methods: Retrospective data from our department were collected on patients who underwent FNB using the Acquire EUS‐FNB needle (Boston Scientific, Massachusetts) and FNA using the EchoTip Ultra EUS‐FNA Needle (Cook Medical, Indiana) between January 2017 and February 2018. The cases were reviewed independently by two cytopathologists and evaluated for the presence of cell block or core tissue material, adequacy for potential ancillary testing, and number of passes. Results: The number of passes ranged from 1 to 16, with a mean of 5.52 ± 3.74 in the FNA group, and from 1 to 6, with a mean of 2.74 ± 1.11 passes in the FNB group ( P  < .0001). Tissue cores were present in 87.23% of the FNB needle samples. A cell block was adequate in 36.36% of cases using the FNA needle. The diagnostic yield as well as the adequacy for ancillary testing were significantly different between the two groups ( P = .0001). The tumor size, location and patients' demographics were not statistically significant between the two groups. Conclusion: Compared with the conventional needle, the new FNB needle was associated with a lower number of passes and a better yield for histological material.